Strategy and action plan for mitigating water disasters in Vietnam (New York, 1994)
Contents: Introduction; current water disasters in Vietnam; Institutional arrangements for mitigating water disasters in Vietnam.
Keywords: Wastewater technology,Công gnhệ xử lý nước